Nitrogen-doped reduced graphene oxide/MoS2 'nanoflower' composites for high-performance supercapacitors. (1st December 2022) - Bokhari, S.W.; Ellis, A.V.; Uceda, M.; Wei, S.; Pope, M.; Zhu, S.; Gao, W.; Sherrell, P.C.
Abstract: Mixed-phase (MP) metal disulfides have interesting electrochemical properties which originate from the generation of the abundance of electrochemically active sites and a higher structural stability as compared with crystalline materials. However, there is less exploration in the design and performance of the MP materials for supercapacitors application. Herein, nitrogen-doped reduced graphene oxide (N-rGO) with MP molybdenum disulfide (MoS2 ) nanoflower (NGM) nanocomposite was self-assembled in a one-pot hydrothermal synthesis. The NGM nanocomposites featured a high surface area and electrical conductivity governed by the uniform growth of nanoflowers on the conductive N-rGO sheets. Coupled with an interconnected network of charge transport channels, the robust ion transport and lowered charge transfer resistance at the electrode-electrolyte interphase significantly boost the electrochemical activity enabling the electrodes to deliver a high specific capacitance (539.5 F g −1 ), exceptional energy and power densities (Pmax  = 25.4 kW kg −1, and Emax  = 71.5 Wh kg −1 ) and excellent capacitance retention of 95.3 % during long-term cycling. Graphical abstract: Multi-phase (1T, 2H, amorphous) MoS2 /N-rGO gives an exceptional performance as a supercapacitor electrode through intimate contact between interconnected 3D networks. Unlabelled Image Highlights: A multi-phase MoS2 /N-doped rGO is designed via hydrothermal self-assembly. The multi-phase MoS2 results in enhanced electrochemical properties. The intimate hierarchical structure shows enhanced structural integrity. High specific capacitance and energy/power densities are achieved.